Direct FE² analysis of additively manufactured parts with voids - Dhari, Rahul; Hall, W.; Asthana, A.; Javankbakht, Z. (2023)
This study challenges the Direct FE² method to model voids in additively manufactured parts. Two sets of polylactic acid (PLA) tensile coupons—without any voids and with 23% voids—were manufactured using fused deposition modelling (FDM) and assessed under monotonic loading. An in-house Python script was developed to implement the modelling steps of Direct FE2 in ABAQUS commercial package. A homogenised medium was used in conventional finite element (FE) method whereas discrete modelling of voids was adopted in Direct FE2. Despite using the same isotropic elastoplastic material model with progressive damage, the response of Direct FE2 was noticeably softer. Although stress concentration around the voids were illustrated in Direct FE2, high error values demand further refinements in selecting the representative volume. The applications of this approach can be extended to modelling defects in other complex parts such as auxetic/sandwich structures and composites.